Reduction of 3-Methyl Pyridinium Bromochromate by C3Alcohols: A Kinetic and Mechanistic Study - HIRAN, B.L.; MALKANI, R.K.; CHAUDHARY, JYOTI; AMB, B.K.; DANGARH, B.K. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of alcohols containing three carbons, i.e., allyl alcohol (prop-2-en-1-ol), 1-propanol and 2-propanol by 3-methyl pyridinium bromochromate in HCIO4-water medium revealed first order each in 3-methyl pyridinium, alcohol and H+. Bunnett-Olsen plots suggest that water acts as proton abstracting agent in slow step. Rate increases by decrease in dielectric constant of solvent and remains unchanged by ionic strength. Products of oxidation are acraldehyde, propanal and propanone from allyl alcohol, 1-propanol and 2-propanol respectively. Activation parameters for rate-determining step have been computed. Keeping awareness of all the experimental observations, mechanism-involving ion-dipole interaction and rate law has been suggested. Order of reactivity of alcohols was observed: Allyl alcohol> 1-Propanol> 2-Propanol.